APLIKASI PENGHUBUNG SUPPLIER DAN SELLER TOKO SHERLY BUSANA - Afandi, Nico (Jurnal Ilmu Komputer dan Sistem Informasi, 2017)
Sherly Busana fashion outlet is a clothing store that sells wide variations of clothing from various brands, such as T-shirts, shirts, long pants, and short pants. Of course, with these wide variations of product, the considerably huge amount of customer is inevitable. The owners of Sherly Busana store, the husband and wife, are both in their fifties and sixties, while the fashion world is a fast-paced industry, leaving no room for the old-fashioned. And that’s exactly the problem which the owners of Sherly Busana store face. This paper offers a solution to the problem that the owners face by designing a web-based applications using the programming language PHP and android-based applications by using waterfall model as the mdel. The making of these applications strive for the success for people who still want to do business in the fashion industry, despite the age.